Doing Business in the European Union 2018 : Croatia, the Czech Republic, Portugal and Slovakia - World Bank Group (World Bank, Washington, DC, 2018)
Doing business in the European Union 2018: Croatia, the Czech Republic, Portugal, and Slovakia focuses on business regulations and their enforcement in five doing business areas. It goes beyond Zagreb, Prague, Lisbon, and Bratislava to benchmark 21 additional cities. This report contains data current as of February 15, 2018 and includes comparisons with other economies based on data from doing business 2018: reforming to create jobs. Doing business measures aspects of regulation that enable or hinder entrepreneurs in starting, operating, or expanding a business - and provides recommendations and good practices for improving the business environment.